Usulan Rancangan Strategy Map Bedasarkan Konsep Balance Scorecard Sebagai Acuan Strategi Pada Sekolah Tinggi X - Tasya Tasya; Dwi Hartanti (Peneliti.net, 2023)
This study aims to assist Sekolah Tinggi X in analyzing and understanding the alignment of new strategies applied with the vision and mission of the College, as well as proposing a design of a strategy map based on a balanced scorecard that can be useful and can be used as a consideration in determining strategies for College X. This research uses a balanced scorecard approach developed by Kaplan and Norton (1996). The research method used in this study is a descriptive qualitative method with two data sources, namely primary data using interview techniques and secondary data obtained through documentation and literature studies. The results of this case study at College X using a SWOT analysis show several strengths, weaknesses, opportunities and threats that the College has and faces, and produces 16 strategic goals classified into four BSC perspectives, including 2 strategic goals from a financial perspective, 3 strategic goals from a customer perspective, 5 strategic goals from a financial perspective. internal processes and 6 strategic goals on a learning and growth perspective. Then the strategic objectives are formed into the strategy map as the final result of this research.